Using French Language Facebook Posts to Increase Beginning Students' Instrumentality and Cultural Interest. Issue 1 (16th March 2018) - Wyatt, Shelly; Gunter, Glenda
Abstract : This quasi-experimental study examined the impact of interactions with native French language Facebook posts on beginning French language learners' attitudes towards the target language and culture. Participants in this study were recruited from two sections of FRE 1120, Elementary French Language and Civilization I at the University of Central Florida. Native French language Facebook posts were 'pushed' to participants' personal Facebook News Feeds over the course of four weeks, with posts pushed on weekdays only. Dörnyei and Clément's (2001) Language Orientation Questionnaire was used to measure participants' attitudes towards the target language and culture. Data were analysed using a split-plot ANOVA. A total of twenty-six participants completed the study, with fourteen participants in the control group and twelve participants in the treatment group. Both sections of FRE 1120 were conducted in a face-to-face modality and were taught by the same instructor. Results indicated that participants' attitudes towards the target language and culture were not significantly impacted by interaction with native French language Facebook posts. Opportunities for future research include increasing the size of the sample, increasing the length of the study, and selecting participants who are more advanced in their mastery of the target language.